PENGARUH NORMATIVE COMMITMENT, AFFECTIVE COMMITMENT DAN CONTINUANCE COMMITMENT TERHADAP SWITCHING INTENTIONS - Kurniawati , (Universitas Trisakti, 2007)
Although research the determinant of service provides switching has grown in recent years, the focus has been predominantly on transactional, not relational variables. In this research, the authors address the role of customer commitment on customers' intentions to switch. Drawing from organizational behavior literature, they build on previous service switching research by developing a switching model that includes a three-component conceptualization of customer commitment. Structural equation modeling is used to test the model based on data from a survey of 198 auto repair service customers. The authors' results support the notion that customer commitment affects intentions to switch service provider and that the psychological states underlying that commitment may differ. As such, future marketing research should consider these different forms of commitment in understanding customer retention. The implications of this model for theory and practice are discussed.Keywords: Normative Commitment, Affective Commitment, Continuance Commitment, and Switching Intentions.